Mo6 cluster-based compounds for energy conversion applications: comparative study of photoluminescence and cathodoluminescence. Issue 1 (31st December 2017) - Dierre, Benjamin; Costuas, Karine; Dumait, Noée; Paofai, Serge; Amela-Cortes, Maria; Molard, Yann; Grasset, Fabien; Cho, Yujin; Takahashi, Kohsei; Ohashi, Naoki; Uchikoshi, Tetsuo; Cordier, Stéphane
Abstract: We report the photoluminescence (PL) and cathodoluminescence (CL) properties of face-capped [Mo6 X i 8 L a 6 ] 2− (X = Cl, Br, I; L = organic or inorganic ligands) cluster units. We show that the emission of Mo6 metal atom clusters depends not only on the nature of X and L ligands bound to the cluster and counter-cations, but also on the excitation source. Seven members of the Ax Mo6 X i 8 L a 6 series (A = Cs +, (n-C4 H9 )4 N +, NH4 + ) were selected to evaluate the influence of counter-cations and ligands on de-excitation mechanisms responsible for multicomponent emission of cluster units. This study evaluates the ageing of each member of the series, which is crucial for further energy conversion applications (photovoltaic, lighting, water splitting, etc.). Abstract :